Board structure, ownership structure, and capital structure: empirical evidence on Shariah and non-Shariah compliant firms in Indonesia - Rahman Bayuny, Ahmad Fadlur; Haron, Razali (Business Perspectives, 2023)
The main purpose of this study is to investigate the impact of board structure and ownership structure on capital structure of Shariah-compliant firms and Non-Shariahcompliant firms in Indonesia. The study used the Generalized Method of Moments to analyze the relationship by applying 2,739 data observations of non-financial companies registered on the Indonesia Stock Exchange. This study uses commissionaire size, director size, female director, female commissionaire, independent director, and independent commissionaire as proxies for board structure, and ownership concentration and government ownership for ownership structure. The results showed that for Sharia-compliant firms, the relevant determinants are all variables of board structure and ownership structure except independent director. For Sharia non-compliant firms, the only non-relevant determinants are female director and commissionaire size. Interestingly, most of the board structure variables in Shariah compliant firms indicate a strong negative relationship with capital structure of firms (except total commissionaire). This may indicate that board structure of Shariah compliant firms strives to lower the leverage level of the firm. This may also indicate that most managers of Shariah compliant firms are risk averse.